Saikosaponin-a Attenuates Oxidized LDL Uptake and Prompts Cholesterol Efflux in THP-1 Cells. Issue 6 (June 2016) - He, Dan; Wang, Hongyan; Xu, Ling; Wang, Xiaoqing; Peng, Kuang; Wang, Lili; Liu, Pixu; Qu, Peng
Abstract : Abstract: Saikosaponins-a (Ssa) is a major bioactive extract of Radix Bupleuri which is a traditional Chinese medicine. The roles of inflammatory response and lipid transportation in the process of atherosclerosis have drawn increasing attention. We explored the regulation of lipid transportation and immune-inflammatory role of Ssa in early atherosclerosis. The antiatherogenic actions and possible molecular mechanisms of Ssa were texted in THP-1 cells. We examined the effect of Ssa on oxidized low-density lipoprotein (ox-LDL)-induced lipid uptake, cholesterol efflux, immune-inflammatory response. THP-1 macrophages were treated with Ssa followed by ox-LDL for 24 hours. Results from western blot showed that Ssa obviously reduced lipoprotein uptake to block foam cell formation and the expression of Density Lipoprotein Receptor-1 and CD36. Ssa also significantly boosted cholesterol efflux and the expression of ATP binding cassettetransporter A1 and peroxisome proliferator-activated receptor γ. The results also indicated that Ssa inhibited ox-LDL–induced activation of AKT and nuclear factor-κB, assembly of NLRP3 inflammasome and production of proinflammatory cytokines. It is suggested that the ability against immune inflammatory response of Ssa is due to modulation of the PI3K/AKT/NF-κB/NLRP3 pathway. In conclusion, this study provides new insight into Ssa's molecular mechanism and its therapeutic potential in the treatment of atherosclerosis.